Nanoscopic materials size-dependent phenomena - Roduner, E. 1947- (RSC Pub., 2006)
Nanotechnology has been hailed as a key technology of the 21st century. This book focuses on a qualitative and quantitative approach, discussing all areas of nanotechnology with particular emphasis on the underlying physico-chemical and physical principles of nanoscience.
Keywords: Nanostructured materials.; Nanoscience.; Nanotechnology.; elektronické knihy; electronic books